2019
DOI: 10.1093/neuros/nyz310_664
|View full text |Cite
|
Sign up to set email alerts
|

What Size Cerebral Aneurysms Rupture? A Systematic Review and Meta-Analysis of Literature

Abstract: INTRODUCTION Size of the cerebral aneurysms is given a considerable weightage in deciding on the management for cerebral aneurysms. Literature on the size of ruptured aneurysms is heterogenous and often contradictory. The purpose of this systematic review was to determine the size of ruptured aneurysms with respect to location. METHODS We conducted a systematic review of literature. The protocol was registered with PROSPERO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Related literature ( Mokin et al, 2019;Beck et al, 2006 ) emphasizes the high risk of rupture for small aneurysms. Interestingly, all of the proposed methods exhibit no false negatives on small-sized aneurysms.…”
Section: Aneurysm Rupture Risk Estimationmentioning
confidence: 99%
“…Related literature ( Mokin et al, 2019;Beck et al, 2006 ) emphasizes the high risk of rupture for small aneurysms. Interestingly, all of the proposed methods exhibit no false negatives on small-sized aneurysms.…”
Section: Aneurysm Rupture Risk Estimationmentioning
confidence: 99%
“…International Study on Unruptured Intracranial Aneurysms (ISUIA) 1 and 2 that reported a negligible -or even no -risk of rupture (in a certain subgroup) for small-sized CA, 6,9,29 a recently published meta-analysis showed that the mean size of ruptured CA reported by most studies was < 7.0 mm, which considerably varies with the aneurysm location. 30 Interestingly, such small size of CA fairly represents the majority of diagnosed aneurysms, and surprisingly, the vast number of ruptured ones. 11-13 Moreover, while larger aneurysms seem to harbor a higher risk for rupture, 8,9,31 (owing physical dimensions), they express their existence earlier via space-occupying nature (compressive effect on nearby structures), on the other hand small-sized aneurysms frequently lack such early mass effect and thus be expressed only when ruptured.…”
Section: Discussionmentioning
confidence: 99%
“…A non-official solution proposed the combination of hemodynamics parameters determined via computational fluid dynamics paired with a 3D surface encoding deep neural network. Related literature [5,27] emphasizes the high risk of rupture for small aneurysms. Interestingly, all of the proposed methods exhibit no false-negatives on small-sized aneurysms.…”
Section: Discussionmentioning
confidence: 99%